Food labelling: hotel culinary professionals' understanding and procurement practices in Malaysia / Siti Nurhayati Khairatun @ Siti Nurhayati Mohd Sharif - Mohd Sharif, Siti Nurhayati (2013)
In coping with exuberant development in foodservice industry, culinary professionals are expected to be adept in their profession. One of the most critical tasks is dealing with procurement practices. Foods procurement appears to be the most indispensable practice in food business operation where cost becomes the uppermost concerns. However, the customers' issues related to health, religious and principle are more discernible than just comparing food prices. Owing to its importance, understanding food labelling requires skills and knowledge rather than just reading for its literal definition. Hence, understanding of food labeling is crucial as it assists the culinary professionals in deciding on the best choice available. A self-administered instrument was sent to all Malaysian registered hotels and resorts via their business emails. The finding of this study reveals that only 54% of the culinary professionals in Malaysia are knowledgeable and there is no significance relationship between their level of understanding and procurement practices. For that reason, it is concluded that their procurement practices was predicated on the norm and tradition established at their respective organisations.